Earth bound A rough guide to the world in picture - Dunford, Martin; Erdpresser, nicola; Jarvis, diana; Sticland, scott (london Penguin Group, 2009)
All of the pictures in Eathbound represent a particular aspect of travel experience
Rough guide photographers have been doing this for years, travelling the world aiming to capture the essence of places and the people who live there in a single photo
Keywords: Travel -- Guide books